2005
DOI: 10.1097/00019501-200509000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from the autopsies of 445 cases of sudden cardiac death in adults

Abstract: In our population, arrhythmia was the most common cause of sudden cardiac death, while acute coronary thrombi and acute myocardial infarction were detected only in some cases. Because of the heterogeneity in the cause of sudden cardiac deaths in adults, a detailed forensic investigation may provide important information on the cause of death and help in the development of primary and secondary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…One large-scale multicentre study demonstrated that acute myocardial infarction is 1.28 times more likely to occur between 06:00 and 12:00 than during the other three 6 h intervals of the day (3). Pathological studies have revealed that acute myocardial infarction is the main cause of death in patients with atherosclerotic disease (4,5). The mechanisms of the phenomena are not yet fully understood, but the circadian clock and clock genes may be involved in the process.…”
mentioning
confidence: 99%
“…One large-scale multicentre study demonstrated that acute myocardial infarction is 1.28 times more likely to occur between 06:00 and 12:00 than during the other three 6 h intervals of the day (3). Pathological studies have revealed that acute myocardial infarction is the main cause of death in patients with atherosclerotic disease (4,5). The mechanisms of the phenomena are not yet fully understood, but the circadian clock and clock genes may be involved in the process.…”
mentioning
confidence: 99%
“…All of these evidences definitively underline the superiority of functional risk stratification compared with an approach based solely on angiographic coronary anatomy. Past and present observations can be partly explained by the limitations of coronary angiography, which has limited sensitivity compared with necropsy studies 12 and intravascular ultrasound investigations. 13 Furthermore, the identification of significant lesions may be confounded by coronary remodeling and by the extraluminal location of some plaques.…”
Section: Functional Risk Assessment Vs Invasive Coronary Angiographymentioning
confidence: 77%
“…4.11). Correlation of these findings with angiographic data and clinical acute coronary artery syndromes [4] can be particularly instructive. Representative sections of pertinent gross findings should be submitted for histological study.…”
Section: Take the Coronary Arteries Off The Heartmentioning
confidence: 98%
“…4.3) will allow the prosector to begin mobilizing the plane of dissection, proceeding from known (where the plain is exposed) to unknown (where the plane is yet to be exposed) in a deliberate manner. 4 Retraction of pericardium with a clamp exposes a plane of adhesion between the pericardium and heart which can then be developed safely by sharp dissection Developing the plane of dissection between the heart and adherent parietal pericardium should be done with a fresh scalpel, holding the back of the scalpel on the heart (or any structure that the prosector does not want to injure) and the sharp Fig. 4.5 Keeping the back of the knife to the heart and the sharp edge in the plane of dissection exposes a vein graft (arrowhead) without injury, even if the presence of the graft was unknown prior to its exposure edge of the knife directed into the plane of dissection (Fig.…”
Section: The Parietal Pericardium May Be "Socked In"mentioning
confidence: 99%